Genetic variability of Blastocystis sp isolates obtained from cancer and HIV/AIDS patients - Tan, T.C.; Ong, S.C.; Suresh, K.G. (2009)
This represents the first study to determine the genetic diversity of Blastocystis sp. among cancer and HIV/AIDS patients. Forty Blastocystis sp. isolates obtained from 20 cancer and 20 HIV/AIDS patients were genotyped by PCR using seven pairs of known sequenced-tagged site primers. Out of the 40 isolates, 38 were identified as one of the known genotypes and two isolates were negative with all the STS primers. Blastocystis sp. subtype 3 which is reported to be associated with disease was found to be predominant among the study subjects.